2018
DOI: 10.22271/ortho.2018.v4.i4i.86
|View full text |Cite
|
Sign up to set email alerts
|

A nature friendly knee arthroplasty for prayer and meditation in Asiatic lifestyle

Abstract: Introduction: India is a country where many religions coexist together. Prayer & meditation form an integral part of Indian lifestyle. Also 90% of India's population lives in the rural areas. Medial compartment osteoarthritis is the most common type of arthritis in India. Total knee replacement has longer rehabilitation time, morbidity and cost. In addition, it doesn't allow squatting and sitting cross legged. With rise in unicondylar knee replacements for medial compartment osteoarthritis, patient's satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The health benefits of yoga have been studied by hundreds of peer-reviewed scientific sources. One study published in the International Journal of Orthopaedics Sciencesstates that yogic meditation done in the sitting cross legged pose, is a promising way to improve cardio-metabolic health and, in a trial, found significant improvements in body-mass index, systolic and diastolic blood pressure, both LDL and HDL cholesterol levels, heart rate, weight, and triglyceride levels, which are all traditionally biometrics that indicate lifestyle disorders like obesity and CVD [6] . Study published in the International Journal of Cardiology, which assessed "the effects of yoga & meditation done in Sitting cross legged pose, impact modifiable biological cardiovascular disease risk factors," found that yoga also improved biometrics like blood pressure, heart rate, respiratory rate, waist circumference, cholesterol, and triglyceride levels, revealing "evidence for clinically important effects of yoga on most biological cardiovascular disease risk factors" [7] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The health benefits of yoga have been studied by hundreds of peer-reviewed scientific sources. One study published in the International Journal of Orthopaedics Sciencesstates that yogic meditation done in the sitting cross legged pose, is a promising way to improve cardio-metabolic health and, in a trial, found significant improvements in body-mass index, systolic and diastolic blood pressure, both LDL and HDL cholesterol levels, heart rate, weight, and triglyceride levels, which are all traditionally biometrics that indicate lifestyle disorders like obesity and CVD [6] . Study published in the International Journal of Cardiology, which assessed "the effects of yoga & meditation done in Sitting cross legged pose, impact modifiable biological cardiovascular disease risk factors," found that yoga also improved biometrics like blood pressure, heart rate, respiratory rate, waist circumference, cholesterol, and triglyceride levels, revealing "evidence for clinically important effects of yoga on most biological cardiovascular disease risk factors" [7] .…”
Section: Resultsmentioning
confidence: 99%
“…It was adopted for studying, eating, praying & meditating or in short any activity that needed composure of mind & stability of body. Yoga has propounded the advantages of Sukhasana or sitting cross legged varying from stability of body needed for long duration tasks to self-realization & self-actualization [6,26] . Yoga says that body is the visible Mind & Mind the invisible body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is more functional allowing squatting, sitting cross legged, has longer survival & is more cost effective with faster recovery, lessor hospital stay etc. [11][12][13][14][15] . In a previous publication from this institute, on investigation of causes of dissatisfied patients of knee Arthroplasty, it was found that although the patient complained of pain around the knee, the source & pain generator were mostly from the spine 1 .…”
Section: Discussionmentioning
confidence: 99%